Ergonomic Assessment and Relationship between Workload and Fatigue in Kitting Section Operators - Nidhar, Ainun; Auberta, Genia; Nursalam, Rachmat; Matahelumual, Marselino; Sjahrul Annas, Muhammad (Journal of Integrated and Advanced Engineering (JIAE), 2024)
In the manufacturing industry, specifically in automotive sector, musculoskeletal disorders (MSDs) account for 11.4% of all workplace injuries. This is primarily due to the high demand for increased production capacity. The process of assembling automotive parts involves manually organizing materials before they are sent to the assembly line. The handling of large material loads and repetitive movements during this kitting process can significantly increase the risk of MSDs. A study was conducted to examine the ergonomic risks associated with the kitting process in a manufacturing environment. The study utilized the Rapid Entire Body Assessment (REBA) method to evaluate kitting operators for potential musculoskeletal disorders (MSDs) related to lifting, carrying, and placing materials during the kitting process. Additionally, kitting operators completed the Nordic Body Map (NBM) questionnaire for self-assessment. According to the REBA results, lifting activities (11 points) posed the highest risk, followed by placing materials (7 points) and carrying materials (4 points). The NBM responses indicated complaints of pain in the hands, shoulders, and back, with NBM scores of 36 and 48 points, signifying a low risk. Immediate action is necessary to reduce MSD complaints among packaging operators based on hazard control analysis. Recommendations have been made for ergonomic interventions, including improving work postures, regulating loads through ergonomic training, utilizing assistive devices, and making workspace adjustments to minimize the risk of MSDs. By implementing appropriate interventions and preventive measures, the risk of MSDs among kitting operators can be reduced, while improving work safety, comfort, and maintaining productivity and process efficiency